2020
DOI: 10.35908/jeg.v5i1.804
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penerapan Good Corporate Governance Dalam Meningkatkan Kinerja Rumah Sakit di Kota Lubuklinggau dan Kabupaten Musi Rawas Dengan Pendekatan Balanced Scorecard

Abstract: <p>Penelitian ini dilakukan pada Rumah Sakit yang berada di Kota Lubuklinggau dan kabupaten Musi Rawas. Tujuan dari penelitian ini untuk mengalisis pengaruh Good Corporate Governance dalam meningkatkan   Kinerja Rumah Sakit  di Kota Lubuklinggau dan Kabupaten Musi Rawas dengan Pendekatan Balanced Scorecard Variabel dependen dalam penelitian ini adalah Kinerja berbasis balanced scorecard (Y). Variabel bebas dalam penelitian ini adalah prinsip-prinsip Good Corporate Governance yang terdiri dari 5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…The existence of good corporate governance will help a company improve a cleaner, transparent and professional management work pattern so that it will improve the organizational performance. This results were confirmed the research of Kesuma & Nurhayati (2020) who found that the implementation of the good corporate governance principles has a significant positive affect to hospital performance. In other words, the implementation of corporate governance in a government agency will increase the value of the agency in the eyes of public.…”
Section: The Implementation Of Corporate Governance Affects To the Rs...supporting
confidence: 89%
See 2 more Smart Citations
“…The existence of good corporate governance will help a company improve a cleaner, transparent and professional management work pattern so that it will improve the organizational performance. This results were confirmed the research of Kesuma & Nurhayati (2020) who found that the implementation of the good corporate governance principles has a significant positive affect to hospital performance. In other words, the implementation of corporate governance in a government agency will increase the value of the agency in the eyes of public.…”
Section: The Implementation Of Corporate Governance Affects To the Rs...supporting
confidence: 89%
“…In a research which conducted by Kesuma & Nurhayati (2020) it was found that the better implementation of corporate governance principles had a significant affect to hospital performance. Potu (2013) found that leadership, motivation and work environment simultaneously had a positive and significant affect on performance.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Puspitha dan Sujana menyatakan prinsip GCG berpengaruh positif terhadap kinerja berbasis BSC [19]. Kesuma dan Nurhayati menyatakan bahwa prinsip GCG berpengaruh positif signifikan terhadap kinerja berbasis BSC [20]. Penerapan prinsip GCG dapat mendorong kinerja, karena dapat memberikan arahan yang baik dalam mengelola perusahaan dan menjamin tindakan manajemen, sehingga efektivitas dan efisiensi pengelolaan perusahaan dapat tercapai serta menciptakan perlindungan terhadap seluruh kepentingan stakeholder.…”
unclassified